Sazonalidade e estrutura de rede de interações entre aves frugívoras e plantas em um fragmento florestal de Cerrado. - Oliveira, Andréia Cristina de (2020)
Frugivory is a mutualistic interaction whose reduction or loss has direct implications on the conservation and biodiversity of communities. Network theory has proven to be an important tool in understanding these interactions within communities. In addition, seasonal variation may influence the quantity and quality of resources available to different animals in the network, changing the network structure. The aim of this study was to analyze the seasonality influence on the frugivory network structure in a forest fragment, to identify the most important species for community and the most representative birds trophic guild. We assumed that seasonality would change the network structure in both seasons. Observations were carried out in a Cerrado forest fragment, where there are well defined dry and wet seasons and fructification mainly during rainy season. Samples were performed from November/2018 to October/2019 through transects and focal observations, observing birds and plants species, and the paired interactions number. Interaction networks were established for both seasons and the nestedness, modularity and specialization of these networks were calculated. A total of 43 plant species, 33 bird species, 186 interactions and 583 feeding records were recorded in 252 observation hours. The networks structure was not altered by seasonality, both network were modular and specialized, and were not nested. The largest number of interactions was recorded in the dry season. The most important bird species were those of omnivorous habit. Cerrado fragments are refuges for frugivorous birds and are important seed banks for zoochory plant dispersal.